Benign mixed tumor of the lacrimal gland - Sadick, Haneen; Riedel, Frank; Naim, Ramin; Gößler, Ulrich; Hörmann, Karl; Bergler, Wolfgang (ORL, 2003)
The accurate clinical diagnosis of benign mixed tumors of the lacrimal gland is important for the proper therapeutic management. We present an adult case with a benign mixed tumor of the orbital lobe of the lacrimal gland, 8 years after periorbital blunt injury. The tumor lesion was diagnosed later in the persisting traumatic tumefaction region. Clinical examination, ultrasonography and MRI revealed a soft-tissue mass with high density and peripheral enhancement over the superior lateral portion of the right eye with expansion to and invasion of the orbital roof and lateral wall. Lateral orbitotomy was performed to resect the tumor. Histopathology disclosed a pleomorphic adenoma of the orbital lobe of the lacrimal gland. Pleomorphic adenomas of the lacrimal gland are seen rarely. The awareness of the clinical and diagnostic features of benign mixed tumors of the orbital lobe should help to avoid complications arising from an incisional biopsy or incomplete tumor resection.